Retrobulbar cellulitis and abscessation: focus on short‐ and long‐term concurrent ophthalmic diseases in 41 dogs. (12th September 2018) - Fischer, M. C.; Adrian, A. M.; Demetriou, J.; Nelissen, P.; Busse, C.
Abstract : Objective: To describe concurrent ophthalmic diseases in dogs with retrobulbar cellulitis and abscessation. Materials and Methods: Retrospective analysis of clinical records of dogs with retrobulbar inflammation. Results: Forty‐one dogs were diagnosed with retrobulbar inflammation; of these, 23 presented with abscessation and two with zygomatic sialoadenitis. Diagnosis was based on orbital ultrasound, MRI, CT and cytological and microbiological examination of fluid or tissue samples. Management involved evacuation of fluid contents using ultrasound‐guided fine‐needle aspiration via the pterygopalatine fossa or orbitotomy. Patients received systemic antibiotics (except for one with sialoadenitis), glucocorticoids, non‐steroidal anti‐inflammatory drugs, opioids and fluid therapy. At initial presentation one or more ophthalmic complications were reported in 19 dogs (46%) including internal ophthalmoplegia (n=5), blindness due to optic nerve damage (n=5), facial nerve paralysis (n=3), prolapse of the third eyelid gland (n=3), corneal ulceration (n=8), anterior uveitis (n=4), chorioretinitis (n=3), retinal detachment (n=2) and increased intraocular pressure (n=7). Information on ophthalmic complications after cessation of active inflammation was available for 33 patients. One or more concurrent disease was found in 10 cases (30%): in addition to persistent neurological deficits and third eyelid gland prolapse reported at initial presentation, visual deficits after retinal re‐attachment (n=2), loss of corneal sensation (n=1), corneal oedema (n=1), corneal fibrosis (n=4), corneal lipidosis (n=1) and strabismus after suspected fibrosis (n=2) were diagnosed. Clinical Significance: Ophthalmic complications are common in patients with retrobulbar inflammation indicating that these patients should undergo ophthalmic assessment and follow‐up.